Astragalus membranaceus Injection Protects Retinal Ganglion Cells by Regulating the Nerve Growth Factor Signaling Pathway in Experimental Rat Traumatic Optic Neuropathy. (18th December 2020) - Wu, Qiong; Gu, Xinyi; Liu, Xinyan; Yan, Xiaoling; Liao, Liang; Zhou, Jian
Abstract : Activation of the nerve growth factor (NGF) signaling pathway is a potential method of treatment for retinal ganglion cell (RGC) loss due to traumatic optic neuropathy (TON). The present study aimed to explore the biological effects of injecting Astragalus membranaceus ( A. mem ) on RGCs in an experimental TON model. Adult male Wistar rats were randomly divided into three groups: sham-operated (SL), model (ML), and A. mem injection (AL). The left eyes of the rats were considered the experimental eyes, and the right eyes served as the controls. AL rats received daily intraperitoneal injections of A. mem (3 mL/kg), whereas ML and SL rats were administered the same volume of normal saline. The TON rat model was induced by optic nerve (ON) transverse quantitative traction. After two-week administration, the number of RGCs was determined using retrograde labeling with Fluoro-Gold. The protein levels of NGF, tyrosine kinase receptor A (TrkA), c-Jun N-terminal protein kinase (JNK), JNK phosphorylation (p-JNK), and nuclear factor kappa-B (NF- κ B) were assessed using western blotting. The levels of p75 neurotrophin receptor (p75 NTR ) and NF- κ B DNA binding were examined using real-time PCR and an electrophoretic mobility shift assay. In addition, the concentrations of JNK and p-JNK were assessed using an enzyme-linked immunosorbent assay. Results . The number of RGCs in ML was found to be significantly decreased P < 0.01 relative to both AL and SL, together with the downregulation of NGF P < 0.01, TrkA P < 0.05, and NF- κ B P < 0.01 ; upregulation of p75 NTR mRNA P < 0.01 ; and increased protein levels of JNK P < 0.05 and p-JNK P < 0.05 . Treatment using A. mem injection significantly preserved the density of RGCs in rats with experimental TON and markedly upregulated the proteins of NGF P < 0.01, TrkA P < 0.05, and NF- κ B P < 0.01 and downregulated the mRNA level of p75 NTR P < 0.01, as well as the proteins of JNK P < 0.05 and p-JNK P < 0.01 . Thus, A. mem injection could reduce RGC death in TON induced by ON transverse quantitative traction by stimulating the NGF signaling pathway.